Implication of weekly and diurnal 14C calibration on hourly estimates of CO-based fossil fuel CO2 ata moderately polluted site in southwestern Germany - Vogel, Felix; Hammer, Samuel; Steinhof, Axel; Kromer, Bernd; Levin, Ingeborg (Tellus. Series B, Chemical and physical meteorology, 2010)
A 7-year-long data set of integrated high-precision 14CO2 observations combined with occasional hourly 14CO2 flask data from the Heidelberg sampling site is presented.
Im Titel erscheint die Zahl 14 hochgestellt und die Ziffer 2 tiefgestellt
Gesehen am 12.09.2023